Bioengineered Nanoparticles for siRNA delivery - Kozielski, Kristen L. (2013)
Short interfering RNA (siRNA) has been an important laboratory tool in the last two decades and has allowed researchers to better understand the functions of non-protein-coding genes through RNA interference (RNAi). Although RNAi holds great promise for this purpose as well as for treatment of many diseases, efforts at using siRNA have been hampered by the difficulty of safely and effectively introducing it into cells of interest, both in vitro and in vivo. To overcome this challenge, many biomaterials and nanoparticles (NPs) have been developed and optimized for siRNA delivery, often taking cues from the DNA delivery field, although different barriers exist for these two types of molecules. In this review, we discuss general properties of biomaterials and nanoparticles that are necessary for effective nucleic acid delivery. We also discuss specific examples of bioengineered materials, including lipid-based NPs, polymeric NPs, inorganic NPs, and RNA-based NPs, which clearly illustrate the problems and successes in siRNA delivery.